PERAN PENDIDIKAN KEWIRAUSAHAAN DALAM MEMEDIASI PENGARUH NORMA SUBYEKTIF TERHADAP NIAT BERWIRAUSAHA - Wedayanti, Ni Putu Ayu Aditya; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 5 No 1 (2016), 2016)
The aim of this study was to describe the influence of subjective norms towards entrepreneurship intention of students of the Faculty of Business Economics at the University of Udayana entrepreneurial education as an intervening variable. This research was conducted at the Faculty of Business Economics Udayana University. that which uses quantitative and qualitative analysis. Amount used as a sample of 160 respondents, using probability sampling techniques, particularly Simple Random Sampling. The data has been collected and processed using analytical techniques Jalur.Hasil research shows that tested each variable has valid and reliable, and have viable models Path test according to analysis so that research can be done. The analysis showed that subjective norms and entrepreneurial education significant positive effect on entrepreneurship intentions and the role of entrepreneurship education is able to mediate subjective norms towards entrepreneurship intentions, this means that subjective norms influence the entrepreneurial intention mediated by entrepreneurship education.
Keywords: niat berwirausaha, norma subyektif, pendidikan kewirausahaan